Lifestyle interventions delivered by eHealth in chronic kidney disease: A scoping review. - Ffion Curtis; James O Burton; Ayesha Butt; Harsimran K Dhaliwal; Matthew M P Graham-Brown; Courtney J Lightfoot; Rishika Rawat; Alice C Smith; Thomas J Wilkinson; Daniel S March (PLoS ONE)
A method of overcoming barriers associated with implementing lifestyle interventions in CKD may be through the use of eHealth technologies. The aim of this review was to provide an up-to-date overview of the literature on this topic. Four bibliographical databases, two trial registers, and one database for conference proceedings were searched from inception to August 2023. Studies were eligible if they reported a lifestyle intervention using eHealth technologies. A narrative synthesis of the findings from the included studies structured around the type of eHealth intervention was presented. Where a sufficient number of studies overlapped in terms of the type of intervention and outcome measure these were brought together in a direction of effect plot. There were 54 included articles, of which 23 were randomised controlled trials (RCTs). The main component of the intervention for the included studies was mobile applications (n = 23), with the majority being in the dialysis population (n = 22). The majority of eHealth interventions were reported to be feasible and acceptable to participants. However, there was limited evidence that they were efficacious in improving clinical outcomes with the exception of blood pressure, intradialytic weight gain, potassium, and sodium. Although eHealth interventions appear acceptable and feasible to participants, there is insufficient evidence to make recommendations for specific interventions to be implemented into clinical care. Properly powered RCTs which not only demonstrate efficacy, but also address barriers to implementation are needed to enhance widespread adoption.